2004
DOI: 10.1111/j.1463-1318.2004.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leakage following routine mesorectal excision for rectal cancer in a national cohort of patients

Abstract: Objective Mesorectal excision is successfully implemented as the standard surgical technique for rectal cancer resections in Norway. This technique has been associated with higher rates of anastomotic leakage (AL) and the purpose of this study was to examine AL in a large national cohort of patients.Methods This was a prospective national cohort study of 1958 patients undergoing rectal cancer surgery with anterior resection in Norway from November 1993 to December 1999.Results The overall rate of AL was 11.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
228
6
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(299 citation statements)
references
References 28 publications
27
228
6
20
Order By: Relevance
“…In general, the global, clinical judgement seems to localize a subset of patients at risk for developing complications in general, whereas many patients with no risk factors at all may develop anastomotic leakage [12]. The risk factors for anastomotic leakage identified by univariate and multivariate analysis in our study corroborate with those found in other studies [1][2][3][4][5][6][7][8]. Similar to these studies, the number of risk factors present in an individual patient appeared to be an important predictor of anastomotic leakage in all anastomoses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the global, clinical judgement seems to localize a subset of patients at risk for developing complications in general, whereas many patients with no risk factors at all may develop anastomotic leakage [12]. The risk factors for anastomotic leakage identified by univariate and multivariate analysis in our study corroborate with those found in other studies [1][2][3][4][5][6][7][8]. Similar to these studies, the number of risk factors present in an individual patient appeared to be an important predictor of anastomotic leakage in all anastomoses.…”
Section: Discussionsupporting
confidence: 88%
“…Clinically relevant anastomotic leakage rates range between 3% and 19% [1,[3][4][5][6][7][8][9]. Anastomotic leakage may remain localized, causing perianastomotic inflammation or abscess formation, or may progress to generalised peritonitis.…”
Section: Introductionmentioning
confidence: 99%
“…Not only, the instant clinical consequences, but also AL carries long-term outcome, such as intra pelvic infection, peritonitis, sepsis, longer hospital stay, considerable extra cost, increased in-hospital morbidity and mortality, impaired pelvic organ function (Eriksen et al, 2005;Lee et al, 2008;Law et al, 2007;Riss et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Identified risk factors include male gender [12,13], tumor location and the level of anastomosis [11][12][13]28], steroid use [21], smoking [13,21], intraoperative adverse events [28], the lack of stoma [11,14,15], preoperative chemoradiotherapy or radiotherapy [12,28], severe bleeding [28], higher American Society of Anesthesiologists grade [21,29], and emergency surgery [29].…”
Section: Drain As An Independent Risk Factor Of Anastomotic Leak?mentioning
confidence: 99%
“…This concept has been advocated by subsequently published, large-scale retrospective studies [9,10]. However, introduction of total mesorectal excision (TME) for rectal cancer surgery has prompted further concern with this issue because of the increased incidence of anastomotic leakage with 10 to 20% [11][12][13][14][15]. The Dutch TME trial [15] demonstrated some supportive data of using pelvic drainage in decreasing anastomotic failure rate and the need for surgical re-intervention.…”
Section: Introductionmentioning
confidence: 99%